AREA OF STABILITY IN SIMILARITY OF PARAMETERS OF DISCRETE SYSTEMS IN THE GIVEN QUALITY INDICATORS - Мовчан, С. Л. (Proceedings of National Aviation University, 2021)
The question of construction of regions of stability of discrete systems with the set indicators of quality in space of parameters which are nonlinearly included in coefficients of the characteristic equation is considered. Due to the use of discrete anayuga of the D-partition method and the developed algorithm, the stability region of a real discrete system with specifically specified indicators of the degree of stability and oscillation is obtained. The proposed approach gives better indicators of the accuracy of determining the area of ​​stability and is more efficient and economical in terms of machine implementation than existing universal numerical methods.